Psihoterapia în arealul monahal – între discreție și necesitate - Irimiea, Arsenie (Alexandru) (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The monastic life asks for great efforts in order to gain the final saving. An abbot has great responsabilities in accepting or refusing the (young) people who want to enter the monastery. Today’s world imposes a great pressure on each person determining mental illnesses. The digital technology is the most serios threat to the monastic life, even though rules are imposed. There are only a few people searching the ideal of a spiritual life within a monastery. This fact makes more difficult an abbot’s decision to encourage a person to stay when it’s obvious that this individual doesn’t have a monastic calling. These situations ask for discernment. Nevertheless, the monastic community needs to preserve its unity no matter what happens. The mental illness can disturb the entire spiritual equilibrium of the monastery. The abbot needs nowadays to have psychiatric knowledge in order to offer real support to the monks he takes care of under the roof of the monastery. In some circumstances it’s better to ask for speciliazed help from outside. Psychoterapy and medical treatment are necessary to solve the arised problems. The monastic life remains a high path of spiritual fulfillment, even in these situations when God allows the struggle of a mental illness.